Conocimientos y actitudes sobre maltrato infantil en alumnado del grado de Odontología - María I, López, María I, López (2020)
Objectives: To evaluate how the current training on pediatric dentistry influences on the knowledge and attitu-des of the students in regards to child abuse and their willingness to report a possible suspicion. Material and methods: The sample consist of 30 students from third-grade and 58 students from fifth-grade enrolled in the Dentistry degree in 2017, with a participation rate of 44.77% for third-graders and 95% for fifth-graders. A self-administered survey was conducted. Descriptive statistics were used as well as the proportions test for two samples, the independent t-test and Wilcoxon signed-rank test to analyze data obtained from the surveys. Results: Students (96.4%) indicated to have received formation regard child abuse. The fifth-graders received more training on the concept of child abuse (p = 0.00) and its diagnosis (p = 0.00), they were more capable of naming six types of abuse (p = 0.00047) and six indicators (p = 0.000) and were more aware of the legal authority to recur for reporting a case as well as the steps to follow. Conclusions: The training received by the students improves their knowledge regarding child abuse and contributes to their motivation for getting actively involved in child protection. However, it does not improve neither their self-confidence to acknowledge a possible case nor their capacity to react against it.